Inhibition of miR-490-5p Promotes Human Adipose-Derived Stem Cells Chondrogenesis and Protects Chondrocytes via the PITPNM1/PI3K/AKT Axis - Li, Hongyi; Zhao, Xiaoyi; Wen, Xingzhao; Zeng, Anyu; Mao, Guping; Lin, Ruifu; Hu, Shu; Liao, Weiming; Zhang, Zhiqi (Frontiers in Cell and Developmental Biology, 2020)
MicroRNAs (miRNAs) play a pivotal role in cartilage development and homeostasis in osteoarthritis (OA). While the fundamental roles of miRNAs in cartilage degeneration have been extensively studied, their effects on chondrogenic differentiation induced by human adipose-derived stem cells (hADSCs) and the underlying mechanisms remain largely elusive. Here, we investigated the roles and mechanisms of miRNAs in hADSCs chondrogenic differentiation and chondrocyte homeostasis. Using microarray analysis, we screened miRNAs expressed in the chondrogenic differentiated hADSCs and identified miR-490-5p as the most significantly down-regulated miRNA. We analyzed its expression patterns during chondrogenesis in vivo and in vitro. Our study showed that miR-490-5p overexpression promoted the transition of hADSCs from chondrogenesis to osteogenesis. In addition, based on miRNA–mRNA prediction analysis and dual-luciferase reporter assay, we proposed and proved that miR-490-5p targeted PITPNM1 by binding to its 3′-UTR and inhibiting its translation. Moreover, loss- and gain-of-function experiments identified the involvement of PI3K/AKT signaling pathway and rescue experiment determined the effect and specific mechanism of miR-490-5p/ PITPNM1/ PI3K/AKT axis in hADSC chondrogenic differentiation and chondrocyte homeostasis. Inhibition of miR-490-5p alleviated cartilage injury in vivo as demonstrated using destabilization of the medial meniscus (DMM) OA model. We identified miR-490-5p, as a novel modulator of hADSC-mediated chondrogenesis and chondrocyte phenotype. This study highlighted that miR-490-5p attenuated hADSC chondrogenesis and accelerated cartilage degradation through activation of PI3K/AKT signaling pathway by targeting PITPNM1. Inhibition of miR-490-5p facilitated hADSCs chondrogenic differentiation and protected chondrocyte phenotype via PITPNM1/PI3K/AKT axis, thus providing a novel stem cell potential therapeutic target for OA treatment.